THE OPTIMIZATION OF CORRUPTION PREVENTION TOWARDS INDONESIA CORRUPTION-FREE - Hibnu Nugroho; Agus Raharjo; Pranoto . (Faculty of Law, Universitas Jenderal Soedirman, 2015)
Prevention and eraducation of corruption case are the strategy which can’t be implemented separatly it should be done synergistically, integrated and concurrently to prevent a new corruptor generation and other new corruptor. So the problem comes on how the strategy which are prevention and eraducation corruption by Indonesian goverment to reach Indonesia free from corruption and what the obsacles in order to reach strategy prevention and eraducation of corruption that already done by Indonesiaan goverment. This research used empirical yuridical method with descriptive analysis, qualitatieve descriptive and conten analysis. By this research can be known that goverment already had preventive and solutive corruption strategy to solve corruption, but there is still be found obstacles such as oerlaping, weak supervison among institution, profesion that related with law enforcemen and not maximal enough witness and informl protection. Keyworld : corruption, prevention, optimalization.